Stress analysis of urban gas pipeline repaired by inserted hose lining method. (15th February 2020) - Lu, Hongfang; Wu, Xiaonan; Ni, Houming; Azimi, Mohammadamin; Yan, Xuanchen; Niu, Yingqi
Abstract: Inserted hose lining (IHL) is a trenchless technology with high application potential in repairing urban gas pipelines. Since the application of this technology in gas pipelines is still in the developing stage, it is necessary to study its feasibility. Based on the mechanical properties of the composite lining material used in this technology, the stress analysis is carried out using ANSYS Workbench software. In this paper, two kinds of aging pipelines with defects are considered, and the repair effect of IHL technology is studied. One is the pipeline with uniform corrosion defect, and the other is the pipeline with corrosion perforation defect. For the pipeline with uniform corrosion defect, the influences of residual thickness, diameter, pressure, and buried depth on pipeline stress are studied. For the pipeline with corrosion perforation defect, the influences of the corrosion perforation position, the corrosion perforation size, diameter, and pressure on pipeline stress are studied. According to the allowable stress of the steel pipeline, the applicable scope of the lining under different conditions is obtained. Based on the analysis results, the main conclusions are as follows: (1) IHL method can effectively reduce the stress of the old pipeline, and the old pipeline is the primary pressure bearing component. (2) Under uniform corrosion conditions, the residual thickness is inversely related to the pipe stress, the pressure and diameter are positively correlated with the pipe stress. (3) Under the condition of corrosion perforation, it is the most dangerous situation that the corrosion hole is near the pipe bottom.